Assessing the structural integrity of the wax-resin lining of The Night Watch using 3D shearography - Tao, Nan; van Duijn, Esther; Vos, Lisette; Steeman, Ilse; Groves, Roger M.; Keune, Katrien; Noble, Petria; Anisimov, Andrei G. (Journal of cultural heritage, 2025)
•For the first time, 3D shearography is used for assessing the structural integrity of the wax-resin lining of The Night Watch.•A safe loading procedure is developed to achieve reliable inspection without risks to the painting.•The developed inspection approach enables the full field monitoring of large-scale wax-resin relined paintings.•Phase compensation process is applied for defect detection.•Vibrations and airflow are the main influencing parameters that affect in-situ shearography measurements. Assessing the structural integrity of cultural heritage objects is of great importance for their structural conservation and long-term preservation. This paper focuses on the development of a non-destructive inspection (NDI) approach using 3D shearography to evaluate the structural integrity of wax-resin lined paintings, specifically for The Night Watch (1642), a large-format 17th-century canvas painting by Rembrandt van Rijn (1606–1669) that is on display in the Rijksmuseum, Amsterdam. The Night Watch has a complex treatment history that has many old repairs of structural defects and damages (holes, tears, etc.) and three wax-resin relinings. In 2021, before a new structural intervention involving retensioning of the canvas support, it was vital to evaluate the structural integrity of the painting, specifically the condition of the treatment carried out in 1975–76 when, among other actions, several long cuts in the area of Captain Frans Banninck Cocq's breeches were repaired and an old canvas insert in the drum was replaced. To assess the structural condition, we applied 3D shearography to quantitatively analyse the in- and out-of-plane surface strains with controlled thermal loading. First, a safe loading procedure was developed by inspecting a representative wax-resin lined test painting where reference delaminations and structural repairs to canvas supports were reliably identified with 3D shearography by raising the temperature with 1-2 °C. As part of Operation Night Watch, in November 2021 an in-situ investigation was carried out in the Rijksmuseum gallery. Two areas of interest in The Night Watch, the restored slashes in the Captain's breeches (0.5 × 1 m) and the canvas insert in the drum (0.2 × 0.5 m), were inspected from the reverse of the painting. Results revealed no critical structural problems associated with the repaired slashes, nor with adhesion of the lining. For the patched canvas in the drum, it showed higher in- and out-of-plane strain variations. Overall, 3D shearography provided valuable non-destructive inspection results for assurances regarding the structural integrity of the 1975 repairs and the adhesion of the lining canvas in The Night Watch.